Photo of the Week - CGIAR Research Program on Climate Change, Agriculture and Food Security (2011)
These photos have been featured on the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) Facebook page 'Cgiar Climate' as 'Photo of the week' paired with a relevant blogstory from CCAFS blog